Latest progress in Van der Waals ferroelectrics - Li Zhengze (MATEC Web of Conferences, 2024)
2D ferroelectrics are regarded as promising materials across diversified aspects such as field-effect transistors (FETs), sensors, and more due to their properties of spontaneous polarization and large, tuneable bandgap. This study presents the latest insights on three representative 2D ferroelectrics: CIPS, SnTe (MX), and h-BN. CIPS exhibits a critical temperature around 315 K, with its spontaneous polarization direction perpendicular to the material sheets. Moreover, the critical thickness of CIPS has been measured at 4nm. SnTe, on the other hand, showcases a critical temperature below room temperature, with a minimum dimension of 5x5 unit cells and polarization oriented along the [110]HJ direction. The ferroelectric behavior of h-BN is attributed to layer sliding, a phenomenon that has garnered significant attention in current research. One notable limitation of 2D ferroelectrics is the presence of critical size or thickness requirements. Additionally, factors like high production costs and poor surface conditions have hindered the practical implementation of these materials in electronic components. Future studies are anticipated to address these challenges and pave the way for the broader utilization of 2D ferroelectrics in various technological applications.